Pengaruh Motivasi Kerja dan Kompensasi Terhadap Loyalitas Karyawan - Rofilah Rahadatul Aisyi; Mudji Kuswinarno (Transformasi: Journal of Economics and Business Management, 2024)
The effect of work motivation and compensation on employee loyalty. High work motivation and fair compensation have proven to play an important role in increasing employee loyalty. High employee loyalty, in turn, can encourage company sustainability in the midst of intense competition. In this research, the method used is a literature review that relies on data from various journals, books, and articles related to the topic. The results show that both work motivation and compensation have a positive and significant relationship with employee loyalty. This suggests that companies need to pay serious attention to both factors to create a supportive work environment. Therefore, companies are advised to strategically manage work motivation and compensation to improve employee productivity and business sustainability, as well as create stronger relationships between employees and organizations.